Comparing Fathers and Mothers Who Have Social Work Contact. - Zhang, Meng Le; Scourfield, Jonathan; Cheung, Sin Yi; Sharland, Elaine (Social Work Research, 2018)
The article discusses a study that examined the attributes of fathers who receive social worker contact using a sample of individuals from a British cohort study, the Avon Longitudinal Study of Parents and Children. Study highlights include the use of classification tree models to predict whether fathers or mothers are more likely to receive social work contact, events associated with social work contact for mothers and fathers, and interaction between age and sex captured by the decision tree.